2022
DOI: 10.1038/s41580-022-00465-y
|View full text |Cite
|
Sign up to set email alerts
|

Apical–basal polarity and the control of epithelial form and function

Abstract: Epithelial cells are the most common cell-type in all animals, forming the sheets and tubes that compose most organs and tissues. Apical-basal polarity is essential for epithelial cell form and function, as it determines the localisation of the adhesion molecules that hold the cells together laterally and the occluding junctions that act as barriers to paracellular diffusion. Polarity must also target the secretion of specific cargoes to the apical, lateral or basal membranes and organise the cytoskeleton and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
148
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 154 publications
(151 citation statements)
references
References 325 publications
2
148
1
Order By: Relevance
“…E-cadherin is not the only form of adhesion molecule that is expressed at cell-cell contacts. A complex network of interactions between the PAR-complex, adhesion molecules, MAGUK scaffolding proteins and the actin cytoskeleton is responsible for building cell-cell junctions (Buckley & Johnston, 2022). Of relevance to this study, PAR-3 has been found to directly bind to transmembrane Junctional Adhesion Molecules (JAMs) and Nectin proteins in mammals (Ebnet et al , 2001; Takekuni et al , 2003; Itoh et al , 2001).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…E-cadherin is not the only form of adhesion molecule that is expressed at cell-cell contacts. A complex network of interactions between the PAR-complex, adhesion molecules, MAGUK scaffolding proteins and the actin cytoskeleton is responsible for building cell-cell junctions (Buckley & Johnston, 2022). Of relevance to this study, PAR-3 has been found to directly bind to transmembrane Junctional Adhesion Molecules (JAMs) and Nectin proteins in mammals (Ebnet et al , 2001; Takekuni et al , 2003; Itoh et al , 2001).…”
Section: Resultsmentioning
confidence: 99%
“…Although the exact mechanisms are still under debate and may differ in different epithelia (Buckley & Johnston, 2022), Laminin, Integrin β1 and RAC1 signalling from the extra cellular matrix (ECM) is now well established to be necessary for directing the overall apico-basal axis of polarisation of internally polarising tubes (Akhtar & Streuli, 2013; Bedzhov & Zernicka-Goetz, 2014; Buckley et al , 2013; Molè et al , 2021; Bryant et al , 2014; Yu et al , 2004). What is less clear is how the precise localisation of the apical membrane initiation site (AMIS) is directed at the single cell level and how this is coordinated between neighbouring cells.…”
Section: Introductionmentioning
confidence: 99%
“…The fundamental function of epithelial cells is to encase internal tissues to protect them from external challenges while allowing for regulated interactions with the environment. A defining feature of metazoan epithelial tissues is the polarization of cells so that the plasma membrane is divided into an apical surface that faces the “external” environment (e.g., the lumen of an epithelial tube or outside of an epithelial sheet) and a basolateral surface that faces internal tissues [reviewed in ( Pickett et al, 2019 ; Buckley and St Johnston, 2022 )]. Cell-cell junctions that reside just below the apical surface tightly link epithelial cells together and provide a selectively permeable barrier [reviewed in ( Vasquez et al, 2021 )].…”
Section: Introductionmentioning
confidence: 99%
“…During fly gut development, ectodermally-derived epithelial tissues such as the hindgut, require the apical polarity determinant Crumbs while endodermally-derived midgut cells lose Crumbs expression ( Tepass et al, 1990 ; Campbell et al, 2011 ) and instead rely on interactions with underlying laminin to correctly polarize ( Tepass and Hartenstein, 1994 ; Yarnitzky and Volk, 1995 ; Pitsidianaki et al, 2021 ). Regardless of the mechanism for apico-basolateral polarity establishment within cells, molecular circuits maintain polarity through positive feedback and mutual antagonism of apical, junctional, lateral, and basal protein complexes ( Pickett et al, 2019 ; Buckley and St Johnston, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation